Linguostylistic Peculiarities of Episode Constructing in Cinematic Prose (on Gr. Greene’s Novel “The Quiet American”) - E. V. Mikhailovskaya; A. Y. Strogaleva (Научный диалог)
The question of the episode as a significant structural and compositional element of cinematic text, which is characterized by a detailed representation of the point of view of a hero, is investigated. An attempt is made to reveal the specifics of the episode structure in the works of the English-speaking writer of the 20th century Graham Greene, whose literary work was closely linked with the cinema. Central episode of Greene’s novel “The Quiet American” (1955) is analyzed as a material. The novelty of the research is seen in the fact that the phenomenon of the cinematography in art prose from the point of view of linguistic style is yet of relatively small degree of scrutiny. In this regard, special attention is paid to the author’s choice of language means in order to achieve the effect of cinematography. It is also noted that for Greene, reflections of the main characters are of great importance, and visual, sonic and other details related to the activities of the human senses serve as an impetus for reflection. The article presents the experience of long-term work of the authors in the field of stylistics of fiction, in particular, deeper study of Gr. Greene’s style was conducted.